1998
DOI: 10.1111/j.2044-8309.1998.tb01181.x
|View full text |Cite
|
Sign up to set email alerts
|

Social identity and individual productivity within groups

Abstract: The purpose of the present research was to show how social identity theory can be applied to enhance individual productivity within groups. Three experiments manipulated in-group identifiability and importance of the group for one's social identity, and compared individual's productivity when working alone to when working in a group setting. The group setting in the first study involved either a collective of unrelated individuals, a group of participants expecting future interaction, or a group working for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
144
1
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(163 citation statements)
references
References 17 publications
13
144
1
5
Order By: Relevance
“…James and Greenberg (1989) found that the individual performance of university students on an anagram task, which would be pooled with that of fellow students, was enhanced when they completed this task in the presence of their university's colors. In a similar vein, Worchel and colleagues (Worchel, Rothgerber, Day, Hart, & Butemeyer, 1998) showed that people's tendency to loaf when working collectively was eliminated if group members wore matching uniforms. In fact, when wearing matching uniforms, individual productivity in a collective setting was higher than when working alone.…”
Section: Ouwerkerk Et Al / Identification and Effort 1551mentioning
confidence: 96%
See 1 more Smart Citation
“…James and Greenberg (1989) found that the individual performance of university students on an anagram task, which would be pooled with that of fellow students, was enhanced when they completed this task in the presence of their university's colors. In a similar vein, Worchel and colleagues (Worchel, Rothgerber, Day, Hart, & Butemeyer, 1998) showed that people's tendency to loaf when working collectively was eliminated if group members wore matching uniforms. In fact, when wearing matching uniforms, individual productivity in a collective setting was higher than when working alone.…”
Section: Ouwerkerk Et Al / Identification and Effort 1551mentioning
confidence: 96%
“…However, both James and Greenberg (1989) and Worchel et al (1998) also found that enhancing the salience of a group by itself is insufficient to increase individual productivity or to enhance social laboring. That is, their results showed that making the ingroup salient only increased people's individual efforts when they were led to believe that their group's performance would be compared with that of another group.…”
Section: Ouwerkerk Et Al / Identification and Effort 1551mentioning
confidence: 99%
“…Plus précisément, l'objectif de cette recherche vise à apporter des éléments de réponse à ces questions en s'appuyant sur les travaux de la psychologie sociale. Sur la base de travaux actuels issus de la Théorie de l'identité sociale (Tajfel et Turner, 1986) et des effets de l'identification sur les motivations et performances (Worchel, Rothgerber, Day, Hart et Butemeyer, 1998), nous nous attendons à ce que la simple catégorisation des élèves dans un groupe et la comparaison à d'autres groupes devrait permettre : la création d'un sentiment d'appartenance à un groupe en ligne, une meilleure coopération et une amélioration des performances collectives.…”
Section: Problématiqueunclassified
“…Another reason is that enhanced to inauthentically high levels social identity resulting from real or potential threat in organizations and society has direct instrumental value for defending individual's psyche against anxiety and other unpleasant feelings. Feelings of common connection in the face of commonly perceived or imagined real or symbolic threat promotes more prosocial behavior, cooperation, social support and conformity among those experiencing the threat (Dovidio & Morris, 1975) and increases individual efforts on behalf of the group, and thus enhances group productivity beyond the authentic levels of individual's initial commitment and self-interest (Worchel, Rothgerber, Day, Hart, & Butemeyer, 1998).…”
Section: Ellemers Spears and Doosje 1999) The Increased (And Somewhmentioning
confidence: 99%